2011
DOI: 10.5402/2011/206103
|View full text |Cite
|
Sign up to set email alerts
|

A Randomised, Cross-Over, Placebo-Controlled Study of Aloe vera in Patients with Irritable Bowel Syndrome: Effects on Patient Quality of Life

Abstract: Background. Irritable bowel syndrome (IBS) is a chronic, difficult to treat condition. The efficacy of Aloe vera in treating IBS symptoms is not yet proven. The purpose of this study was to determine if Aloe vera is effective in improving quality of life. Methods. A multicentre, randomised, double-blind, cross-over placebo controlled study design. Patients were randomised to Aloe vera, wash-out, placebo or placebo, washout, Aloe vera. Each preparation (60 mL) was taken orally twice a day. Patient quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
0
25
0
1
Order By: Relevance
“…Finally, 3 prospective RCTs were included in the meta-analysis after excluding a single-arm study. [6][7][8] Because the numeric outcomes could not be extracted from 1 study included in this meta-analysis, we collected additional unpublished data from the corresponding author. 7…”
Section: Results Of Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 3 prospective RCTs were included in the meta-analysis after excluding a single-arm study. [6][7][8] Because the numeric outcomes could not be extracted from 1 study included in this meta-analysis, we collected additional unpublished data from the corresponding author. 7…”
Section: Results Of Searchmentioning
confidence: 99%
“…Data from the IBS symptom scores before and after treatments were retrieved on different scales from the included RCTs. As in the study by Hutching et al, 7 unreported data were included in this meta-analysis. Moreover, data associated with the second treatment period were excluded from this meta-analysis because of concerns about the carry-over effect.…”
Section: Mean Differences In Irritable Bowel Syndrome Symptoms Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…This improvement, though not statistically significant, continued for up to 2 months posttreatment. 47 In 2011, Hutchings et al 48 found that the consumption of 60 mL of Aloe vera juice twice daily for 5 months did not significantly improve QoL and general symptom scores compared with placebo. Both of these studies present multiple weaknesses including small sample sizes, large patient withdrawal because of increased symptoms with Aloe vera ingestion, loss at follow-up, and short duration.…”
Section: Aloe Vera Gelmentioning
confidence: 98%
“…The following antioxidants have also been examined, but there is insufficient evidence concerning their benefits: Aloe vera [86][87][88][89] Andrographis paniculata [90,91] , bilberry [92,93] , Capsicum [95][96][97] , carnosine [98] , ferrous fumarate [99] , green tea [100] , kiwifruit [101] , mastic gum [102] , N-acetyl cysteine [103] , oxpentifylline [104] , pomegranate [106] , psyllium [107,108] , Pycnogenol [109] , resveratrol (red wine) [110] , superoxide dismutase [11,111] , and tormentil [112] ( Table 1 ).…”
Section: Peppermintmentioning
confidence: 99%